Environmental drivers of ant species richness and composition across the Argentine Pampas grassland - Ramos, Carolina Samanta (2018)
Understanding the underlying mechanisms causing diversity patterns is a fundamental objective in ecology and science-based conservation biology. Energy and environmental-heterogeneity hypotheses have been suggested to explain spatial changes in ant diversity. However, the relative roles of each one in determining alpha and beta diversity patterns remain elusive. We investigated the main factors driving spatial changes in ant (Hymenoptera, Formicidae) species richness and composition (including turnover and nestedness components) along a 500 km longitudinal gradient in the Pampean region of Argentina. Ants were sampled using pitfall traps in 12 sample sites during the summer. We performed a model selection approach to analyse responses of ant richness and composition dissimilarity to environmental factors. Then, we computed a dissimilarity partitioning of the contributions of spatial turnover and nestedness to total composition dissimilarity. Temporal habitat heterogeneity and temperature were the primary factors explaining spatial patterns of epigean ant species richness across the Pampas. The distance decay in species composition similarity was best accounted by temperature dissimilarity, and turnover had the greatest contribution to the observed beta diversity pattern. Our findings suggest that both energy and environmental-heterogeneity-related variables are key factors shaping richness patterns of ants and niche-based processes instead of neutral processes appear to be regulating species composition of ant assemblages. The major contribution of turnover to the beta diversity pattern indicated that lands for potential reconversion to grassland should represent the complete environmental gradient of the Pampean region, instead of prioritizing a single site with high species richness.